Calidad educativa como resultado de los centros educativos eficaces - Córdova Alarcón, Melissa Inés (2010)
The educational quality is one of the major concerns in education. This papers show how schools should improve their standards by combining efforts and mechanisms that positively affect the schools' activity in order to improve it in an organized and efficient manner.